The synopsis of the genus Tulipa (Liliaceae) in Uzbekistan - Tojibaev, Komiljon; Dekhkonov, Davron; Ergashov, Ibrokhimjon; Sun, Hang; Deng, Tao; Yusupov, Ziyoviddin (Phytotaxa, 2022)
Uzbekistan is widely regarded as one of the most diversified sources of the species of Tulipa L. The present study provides the synopsis of the genus Tulipa in this area. According to literature reviews and field surveys, this genus includes 33 species (34 taxa) distributed in Uzbekistan. In this paper, more than 3,500 herbarium specimens deposited in the National Herbarium of Uzbekistan (TASH), Komarov Botanical Institute St. Petersburg, Russia (LE), Moscow State University, Russia (MW), Herbarium of the Institute of Botany and Phytointroduction in Almaty, Kazakhstan (AA) and Herbarium of the Institute of Biology in Bishkek (FRU) were utilized to provide comprehensive genus coverage. The evaluation of their distribution and taxonomic classification were described. The taxonomical analyses, diagnostic keys at sectional and species levels as well as morphologic illustrations of most species distributed in Uzbekistan are provided.